Ramificações dos nervos supraescapular e subescapulares cranial e caudal em javalis (Sus sus scrofa Linnaeus, 1758) - Oliveira Júnior, Raul Marcos Pereira de (2009)
The wild boar (Sus sus scrofa) stands out for being very appreciated by men in cooking, thanks to its quality and low rates of cholesterol. Before the scarce literature about its morphology, it was aimed in this work to report the muscles innervated by the suprascapular nerve and subscapulares nerves showing the quantity of branches. There were used 19 animals, originated from the Laboratory of Research in Wild Animals from the Veterinary Medicine College in the Federal University of Uberlândia, concentrated on solution of formol 10%, and after injections of the above-mentioned solution in the carotids arteries , intramuscular and cavities, the muscles of the forelimb were dissected making easy the observation of this innervations. The conclusions were that the suprascapular nerve issued branches to the supraspinal and infraspinal muscles, as the cranial and subscapulares nerves and the tail end, issued branches to the subscapular muscles.